On the buckling crossover of thick-walled pipe bend under external pressure. (15th December 2022) - Yu, Yang; Ma, Wentao; Yu, Jianxing; Li, Zhenmian; Tian, Bowen; Shang, Wenyuan
Abstract: Pipe bend is a common junction in pipeline system. In this study, the post-buckling behavior of deep-sea thick-walled pipe bend under external pressure is studied by numerical simulation. A 4-node tetrahedron solid element based on vector form intrinsic finite element method (VFIFE) is introduced to simulate the whole buckling process. First, the VFIFE models of the thick-walled pipes are built and the results of the VFIFE method, traditional finite element method, and the experiments from other publications are compared to verify the proposed method. Then, collapse modes and collapse mechanism of the pipe bend when buckling propagates to the elbow under dynamic and quasi-static conditions are analyzed. Finally, the influence of different geometric parameters on the crossover pressure of the pipe bend is studied. These results can be used to support the buckling arrest design of pipe bends. Highlights: Analysis of post-buckling behavior of pipe bend based on VFIFE tetrahedral solid element. A self-contact algorithm for the collision of the inner wall of pipe based on VFIFE tetrahedral solid element. The collapse mode and collapse mechanism of pipe bend is analyzed. The influence of transition zone on post-buckling critical pressure is discussed. Effect analysis of the relative bend radius, the diameter–thickness ratios, and the bend angle.